Ochotona (Pika) princeps subsp. princeps Richardson 1828 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Ochotona (Pika) princeps subsp. princeps Richardson 1828 Ochotona (Pika) princeps subsp. princeps Richardson 1828, Zool. J., 3: 520. Type Locality: "Rocky Mountains"; restricted by Preble (1908) to "near the sources of Elk (Athabasca) River," [Athabasca Pass, head of Athabasca River, Alberta, Canada]. Synonyms: Ochotona (Pika) princeps subsp. cuppes Bangs 1899; Ochotona (Pika) princeps subsp. goldmani Howell 1924; Ochotona (Pika) princeps subsp. levis Hollister 1912; Ochotona (Pika) princeps subsp. lutescens Howell 1919; Ochotona (Pika) princeps subsp. obscura Long 1965; Ochotona (Pika) princeps subsp. saturata Cowan 1955. Discussion: Allozyme studies revealed 4-5 main groups of populations in this species (Hafner and Sullivan, 1995). This name belongs to the Northern Rockies group. Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Lagomorpha, pp. 185-211 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 191, DOI: 10.5281/zenodo.7316519